Playful or gameful?: creating delightful user experiences - Lucero, Andrés; Karapanos, Evangelos; Arrasvuori, Juha; Korhonen, Hannu (My University, 2014)
Experts state that research on playfulness and gamification has looked at video games to create better user experiences from user interfaces. Researchers are making efforts to understand how playfulness can be employed in creating meaningful and memorable experiences for users. Playfulness is an important, but neglected design quality for all kinds of products. Features that make games and play engaging can also make other kinds of products more enjoyable, elicit more meaningful experiences from them and increase the quality of the overall user experience along with market value of a product. Playfulness can be a positive feature in products that goes beyond pure entertainment. Gamification has been looking at the use of game-design elements, including points, levels, achievements, leaderboards, and rewards in non-game contexts to motivate and increase user activity and retention.
Keywords: User interfaces; Design Quality; Gamification; Market values; Positive features; User activity; User experience; Video game; Human computer interaction